Effect of vine‐shoots toasting on the generation of high added value volatiles. (11th February 2016) - Sánchez‐Gómez, R.; Zalacain, A.; Alonso, G. L.; Salinas, M. R.
Abstract: This paper shows the volatile composition changes of two vine‐shoots cultivars (a neutral, Airén, and an aromatic, Moscatel) when are subjected to different toasting treatments: light (180 °C for 15 min), medium (180 °C for 30 min) and high (180 °C for 45 min). The vine‐shoots volatile profile for both vine‐shoots varieties was determined by HS‐SBSE‐GC/MS and compared with those of the oak wood used as reference. Results indicated that the higher the toasting, the greater the increment of most wood and varietal volatiles. The vine‐shoots wood volatile composition was similar to the oak one, which is known to be very valuable in case of oak aged wines. The volatiles responsible for a varietal contribution were interesting in both vine‐shoots, especially the well‐known Moscatel particular aroma that showed up at medium toasting. These results suggest the potential exploitation of vine‐shoots to be used with oenological purposes for their high added volatile contribution. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Different toasting intensities affect the volatile composition of two vine‐shoots cultivars (Airén and Moscatel). The higher the toasting, the greater the increment of most wood and varietal volatiles. The volatiles responsible for a varietal contribution were especially relevant for Moscatel and wood volatiles were more significant for Airen vine‐shoots. These results suggest the potential exploitation of vine‐shoots to be used with oenological purposes for their high added volatile contribution in the same way oak wood are used.